The Effectiveness of Assertive Training in Improving Assertive Behaviour in Peer Counselors - Kirana, Dyah Luthfia; Mutiah, Riska; Prayona, Baiq Arwindy (Psikopedagogia, 2024)
The inability to express feelings, difficulty and confusion in making decisions, fear of making mistakes, and dependence on the approval of others are common challenges faced by peer counselors. This research aims to enhance the ability of peer counselors to behave assertively through assertiveness training. The research method used is pre-experimental with a one-group pretest-posttest design. The study involved 14 peer counselors as research subjects. The instrument used is the Assertive Behavior Inventory, which consists of 33 statement items. The research findings indicate that assertiveness training interventions can improve assertive behavior. This is evidenced by the results of the paired sample t-test, which show that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This suggests a significant difference in assertive behavior between the pre-test and post-test results, confirming the effectiveness of assertiveness training in enhancing assertive behavior among peer counselors. This study highlights the importance of strengthening peer counselor competencies, particularly assertive behavior skills, which play a crucial role in the success of the peer counseling service process.